Cervical Pain and its Intensity due to the use of Hand-Held Electronic Devices among University Students - Farida Ali, Muhammad Hussain Iqbal, Fariha Khalid, Ayesha Arooj, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cervical Pain is the pain in the cervical region. It is the 4th leading cause of disability and it affects the young adults due to the poor posture. It is more common in females. Today. The hand-held devices such as cellphone is a necessity for communication, academic and official activities and for leisure time. The more usage of these devices in poor posture is leading to pain which if remain untreated can be a cause of long term impairment or disability. Aim: To find the cervical pain due to the use of hand-held electronic devices among university students. Methods: This cross-sectional study was done on 700 university students. This sample size was calculated by variables: precision 0.05, estimated proportion 0.41 and with confidence level 0.99. A self-administered Questionnaire in English was given to the students fulfilling the eligibility criteria. Results: Among 700 students, 679(97%) use smartphones while 21(0.3%) don’t use smartphones. The percentage of daily usage of smartphones among students was 12.6% for 1-2 hours, 28% for 2-3 hours and 59.4% more than 3 hours daily. The neck pain was reported in 500 (71.4%) participants whereas 200 (28.6%) had no neck pain. The participants rated pain on VAS Scale as 200 (28.6%) answered no pain, 434 (62%) answered Moderate Pain and 66 (9.4%) answered Worst Pain. Conclusion The results of this study concluded that there was strong association of cervical pain with daily usage of smartphone.